Dual‐Source Precursor Approach for Highly Efficient Inverted Planar Heterojunction Perovskite Solar Cells. Issue 19 (15th March 2017) - Luo, Deying; Zhao, Lichen; Wu, Jiang; Hu, Qin; Zhang, Yifei; Xu, Zhaojian; Liu, Yi; Liu, Tanghao; Chen, Ke; Yang, Wenqiang; Zhang, Wei; Zhu, Rui; et al.
Abstract : The highest efficiencies reported for perovskite solar cells so far have been obtained mainly with methylammonium and formamidinium mixed cations. Currently, high‐quality mixed‐cation perovskite thin films are normally made by use of antisolvent protocols. However, the widely used "antisolvent"‐assisted fabrication route suffers from challenges such as poor device reproducibility, toxic and hazardous organic solvent, and incompatibility with scalable fabrication process. Here, a simple dual‐source precursor approach is developed to fabricate high‐quality and mirror‐like mixed‐cation perovskite thin films without involving additional antisolvent process. By integrating the perovskite films into the planar heterojunction solar cells, a power conversion efficiency of 20.15% is achieved with negligible current density–voltage hysteresis. A stabilized power output approaching 20% is obtained at the maximum power point. These results shed light on fabricating highly efficient perovskite solar cells via a simple process, and pave the way for solar cell fabrication via scalable methods in the near future. Abstract : A dual‐source precursor approach is developed to fabricate a high‐quality and mirror‐like mixed‐cation perovskite without involving additional antisolvent process. By integrating the perovskite films into the planar heterojunction solar cells, a power conversion efficiency of 20.15% is achieved with negligible hysteresis effect. A stabilized power output approaching 20% is obtained at the maximum power point.